Effects of Technological Change and Institutional Reform on Production Growth in Chinese Agriculture - Fan, Shenggen (Wiley, 1991)
Recent rapid agricultural production growth in Chinese agriculture could be attributed to an increase in inputs, technological change, and institutional reform. An accounting approach was used to separate the relative contribution of these three factors. Institutional change, like the introduction of the household production responsibility system, has contributed to past growth in production. However, technological change is crucial to furthering production growth because of the limited potential for significant increase in the use of conventional inputs, in particular land. Continued institutional change must accompany corresponding technological changes.